Very mild exposure to hypoxia for 8 h can induce ventilatory acclimatization in humans. - Fatemian, M; Kim, D; Poulin, M; Robbins, P (2001)
Ventilatory acclimatization to altitude is associated with a progressive increase in ventilation, a progressive decrease in end-tidal PCO2 and a progressive increase in the acute ventilatory sensitivity to hypoxia. Ventilatory acclimatization has been observed with mild exposure to hypoxia when the duration of exposure has been of some length (e.g. days), and with shorter duration exposures (e.g. 8 h) when the degree of hypoxia has been more severe. The purpose of this study was to determine whether short-duration exposures to very mild hypoxia, such as are commonly associated with the reduction in cabin pressure during commercial airline flight, can also induce some degree of ventilatory acclimatization. Twelve subjects were exposed in a chamber to both 8 h mild hypoxia (inspired PO2 127 mmHg) and 8 h air-breathing as a control. Exposures were on different days in random order. Following the hypoxic exposure, there was a significant reduction in end-tidal PCO2 during air breathing (from 39.2+/-1.8 to 38.11+/-1.5 mmHg, mean +/- SD, P<0.05), and a significant increase in ventilatory sensitivity to hypoxia (from 0.84+/-0.54 l/min/% to 1.13+/-0.66 l/min/%, P<0.05). We conclude that shortterm exposures to very mild hypoxia do induce significant acclimatization within the respiratory control system.